RANCANG BANGUN ALAT WIRING DIAGRAM THRUST REVERSE ENGINE SYSTEM BOEING 737-200 SEBAGAI MEDIA PEMBELAJARAN DI POLITEKNIK PENERBANGAN SURABAYA - Gilang Lailul Akbar (Politeknik Penerbangan Surabaya, 2021)
Thrust reverser is a system that can reverse the direction of the engine thrust from the engine fan air exhaust to the front. One of the functions of the thrust reverser is to assist the aircraft in braking. Making this wiring diagram aims to help aircraft engineering cadets understand how thrust reverse works. There are several things that must be understood before this Trust Reverse system is operated. When a pilot or a technician wants to control, foward or reverser on thrust reverse. must pay attention to the fire extinguisher switch on the engine, oil pressure conditions, landing gear position and hydarulic pressure conditions. When a technician wants to control thrust reverse on an aircraft for maintenance, you can use an overide switch located on the overhead panel of the cockpit. The results of wiring diagram the reverse thrust wiring diagram test show that thrust reverse can be operated when the fire extinguisher switch on the engine is under pressure, the oil pressure is not low, the landing gear has touched the ground and there is hydarulic pressure as a driving force. The overide switch can be operated without pay attention that the landing gear has touched the ground and low oil pressure